2017
DOI: 10.1177/1359105317739100
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress and life satisfaction in mothers of children with cerebral palsy: The mediating effect of social support

Abstract: In this study, we investigated the mediating effect of social support on the relationship between parenting stress and life satisfaction in Chinese mothers of children with cerebral palsy ( N = 369). The results showed that family support and friend support, but not significant-other support, had mediating effects on the relationship between parenting stress and life satisfaction. Moreover, the mediating effect of friend support was equal to family support. These results suggest that the focus should be on red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 56 publications
4
44
0
7
Order By: Relevance
“…Of the 13 articles, 6 explored parental stress as an outcome measure (Bannink et al, 2016; Ma et al, 2017; McCabe and McCabe, 2013; McNally and Mannan, 2013; Tilahun et al, 2016; Wang et al, 2017). In these studies, researchers found that parental stress was negatively related to parents’ perceived support from different informal sources such as family, friends, community members, and parents support group, with the authors suggesting that greater satisfaction with support was associated with less stress (Bannink et al, 2016; Ma et al, 2017; McCabe and McCabe, 2013; Wang et al, 2017). Parental stress had a strong negative correlation with support from immediate family members among these informal support sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 articles, 6 explored parental stress as an outcome measure (Bannink et al, 2016; Ma et al, 2017; McCabe and McCabe, 2013; McNally and Mannan, 2013; Tilahun et al, 2016; Wang et al, 2017). In these studies, researchers found that parental stress was negatively related to parents’ perceived support from different informal sources such as family, friends, community members, and parents support group, with the authors suggesting that greater satisfaction with support was associated with less stress (Bannink et al, 2016; Ma et al, 2017; McCabe and McCabe, 2013; Wang et al, 2017). Parental stress had a strong negative correlation with support from immediate family members among these informal support sources.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies explored the interconnections between life satisfaction and social support that consisted of physical, emotional, informational, and instrumental assistance that an individual received from their social network (Lu et al, 2015; McNally and Mannan, 2013; Wang et al, 2017). Among these three studies, two were quantitative and measured the mediating effect of social support on life satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Social support is associated with better quality of life and acts as a significant indicator of the subjective well-being among people with substance abuse disorder ( 36 ). Wang et al ( 37 ) found that the relationship between stress and life satisfaction can be mediated by support from family and friends, but not from a person's significant other. Stress is associated with life satisfaction by increasing the demand for social support.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that demographic variables, such as gender, age, and education (e.g., Checa, Perales, & Espejo, 2018), and personal variables, such as self-esteem, optimism, and resilience (e.g., Chen et al, 2017), could strongly predict individuals life satisfaction. Individuals with higher levels of life satisfaction reported higher levels of self-esteem (Chen et al, 2017) and optimisms (Kapikiran, 2012), obtained lower levels of anxiety (Brailovskaia, Schönfeld, Kochetkov, & Margraf, 2018) and distress (Wang, Huang, & Kong, 2017), and received more social support from family and friends (Kong et al, 2015). Among these factors that affect life satisfaction, social anxiety is one of the examined variables for life satisfaction (Lu, Zhen, Li, Hong, & Ling, 2019).…”
mentioning
confidence: 99%